2018
DOI: 10.2147/iprp.s142982
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy travel health services: current perspectives and future prospects

Abstract: Rates of international travel are increasing annually, with particular growth observed in travel to Southeast Asia and to emerging economies. While all patients traveling across geographic regions are recommended to receive a pre-travel consultation to consider their individual risks, many do not, or receive care and recommendations that are not consistent with current evidence-based guidelines. As experts in drug therapy, and given the largely preventive nature of most travel health recommendations, pharmacis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 29 publications
3
14
0
Order By: Relevance
“…Several investigations on the knowledge, attitudes, and behavior of the general population and physicians regarding travel medicine have been conducted in different countries [4][5][6], and, to date, there is also research on the involvement of community pharmacists in this field [7][8][9][10][11][12][13][14][15][16]. This is of utmost importance in order to provide important information for planning training interventions targeted towards these professionals to positively affect travelers' health.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations on the knowledge, attitudes, and behavior of the general population and physicians regarding travel medicine have been conducted in different countries [4][5][6], and, to date, there is also research on the involvement of community pharmacists in this field [7][8][9][10][11][12][13][14][15][16]. This is of utmost importance in order to provide important information for planning training interventions targeted towards these professionals to positively affect travelers' health.…”
Section: Introductionmentioning
confidence: 99%
“…International travel is on the increase, especially to destinations in Asia, Africa and other emerging economies and the associated health risks of these destinations highlights the need for pre-travel health consultations [ 1 , 2 ]. Despite this, many travellers do not obtain pre-travel health advice before travelling overseas and, those who do, mainly seek advice from their general practitioner, a travel health clinic or specialist, or the internet [ 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Houle, in a review on current and future prospects for travel health services, indicated the role that pharmacist have been playing in ensuring the cold chain for vaccinations has placed them in a good position to extend their scope of practice from administering just the influenza vaccine to travel vaccines [ 2 ]. This has already been adopted in some Canadian jurisdictions [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Related to pharmacists' need for further training or education in travel medicine, the complexity of travel medicine (for example, regional differences in disease epidemiology, outbreaks, and changes in resistance patterns for infectious diseases) and need for individualized care is noted by pharmacists. Many preliminary studies have identified this barrier and suggest that a gap in training in pharmacy school curricula is a contributor [15][16][17][18]. Pharmacy schools across the US and Canada do not have robust travel medicine competencies built into their core curricula, apart from immunization training, which tends to focus on influenza and other routine vaccinations [15][16][17][18].…”
mentioning
confidence: 99%
“…Many preliminary studies have identified this barrier and suggest that a gap in training in pharmacy school curricula is a contributor [15][16][17][18]. Pharmacy schools across the US and Canada do not have robust travel medicine competencies built into their core curricula, apart from immunization training, which tends to focus on influenza and other routine vaccinations [15][16][17][18]. This lack of exposure during pharmacists' training years as students likely impacts the provision of these services upon licensure.…”
mentioning
confidence: 99%